Kebijakan Perijinan Usaha Industri Di Kota Medan - Revida, Erika (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2006)
Industrial effort is an urgen sentra and important to increase especially in government of Medan City North Sumatera. Besides can improve Earning of Genuiness Area (PAD), industrial effort can also accomodate labours and increase economic climate. But in practice, the policy of industrial effort permit in government of Medan City North Sumatra must have strong komitment and good willingness to make the policy of market friendly industrial effort permission.